Impact on the activity of rare disease organisations and their relatives during the COVID-19 containment in Spain - Guerra, José Manuel; Coca, Juan R. (Acciones e Investigaciones Sociales, 2021)
The COVID-19 pandemic has become a health crisis, with wide-ranging repercussions. Rare disease (RD) services have been affected by the changes resulting from the measures for their management. This study has analysed the impact of strict containment on the services and activity of RD-related organisations. A total of 81 RE entities in Spain participated in the study. The results showed that there has been a negative effect on the number of activities and services that the entities have been able to provide during this period. This was due both to the elimination of these activities and services and to the changes that had to be made in order to be able to provide them.